Penerapan model pembelajaran kooperatif tipe JIGSAW menggunakan media LKS untuk meningkatkan hasil belajar matematika siswa V SDN 03 Batursari - Tri Aristanti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The formulation of the problem of this research is whether the Jigsaw cooperative learning model with LKS media can improve student learning outcomes in class VA SDN 03 Batursari?.This research is a classroom action research and is designed in two cycles, each cycle is carried out in the stages of planning, implementation, observation and reflection. The results of the study are as follows: 1) The results of observations on student activity in the first cycle were 61.75% in the second cycle to 85.38%. 2) The results of observations of teachers in the first cycle were 66% in the second cycle to 89%. 3) The results of the evaluation tests in the first cycle of students who finished studying were 63% in the second cycle to 99%, while the average grade value in the first cycle was 63.98 in the second cycle to 78.4. Based on the results of this study, teachers should apply the Jigsaw type cooperative learning model with LKS media so that it can improve student learning outcomes.